Hospitalization, mortality, and health service delivery pattern among Iranian Hajj pilgrims by age, sex, and province in 2013–22 - Pirhossein Kolivand; Pirhossein Kolivand; Peyman Saberian; Jalal Arabloo; Peyman Namdar; Taher Doroudi; Taher Doroudi; Ali Marashi; Masoud Behzadifar; Fereshte Karimi; Soheila Rajaei; Behzad Raei; et al. (Frontiers in Public Health)
BackgroundThis study aims to investigate the patterns of hospitalization, mortality, and services provided to Iranian Hajj pilgrims from 2013 to 2022 by age, sex, and province.MethodsWe conducted a pooled cross-sectional study in 2023, encompassing all Iranian Hajj pilgrims from 2013 to 2022. We examined pilgrim hospitalization by age, sex, and province using a Poisson regression model, incorporating demographic variables. Data extraction was performed using file reading methods, and analysis using Excel 2019 and SPSS 27 software.ResultsThe highest mortality among Iranian pilgrims was recorded in 2015 (N = 509, 74.3%), primarily affecting those aged 45–70 (N = 442, 64.5%). Male pilgrims experienced a greater mortality count (580, 84.7%) compared to female pilgrims (105, 18.1%). The main causes of death by province were the Mina stampede and cardiovascular diseases (CVDs). The number of hospitalizations reached its highest level in 2019 (89,492 cases) and was at its lowest in 2022 (38,947 cases). Tehran province reported the greatest number of hospitalizations (73,168 cases), while Ilam (723 cases) and Kohgiluyeh and Boyer-Ahmad provinces (868 cases) had the fewest. With the exception of heart attacks, other factors significantly impacted the average number of pilgrim hospitalizations at a 5% error level. For instance, the hospitalization figure for female pilgrims was 0.73 times that of male pilgrims, and each additional unit of pilgrimage contributed to a 0.05% increase in hospitalizations.ConclusionsTackling the public health challenges associated with mass gatherings is crucial for protecting the health of attendees and ensuring the safety of communities. Effective strategic planning, focused interventions, and strong health surveillance systems are essential to reduce risks and build resilience for future events